Hipótesis sobre el (des)encuentro entre la investigación artística y la investigación científica - Fuentes Cid, Sara (2021)
Fortunately, artistic research has become more accepted by academia in recent years and the potential for a mutually beneficial relationship between art and science seems more promising than ever. Despite this, tensions and reluctance continue to exist that excessively hinder the development of interdisciplinary projects where Art is involved. In this paper we will try, in the first place, to analyze comparatively artistic research and scientific research in the light of four classic domains of the Philosophy of Science: language, mereology, method and truth; secondly, we will formulate two hypotheses about the reasons for the persistent disagreement between art and science, based on the separation between rationalism and empiricism and, on the possibility of encounter, based on the speculative use of reason, between the artistic and scientific research; two methodologically different views on the same concepts or metaphysical problems.